Distributed consensus of the nonlinear second-order multi-agent systems via mixed intermittent protocol. (November 2018) - Guo, Wanli; Xiao, Haijun
Abstract: The leader-following consensus problem for second-order multi-agent systems is investigated in this paper. The topology of the system is directed and the dynamics of each agent is nonlinear. Based on the intermittent control strategy and the adaptive control method, a mixed protocol for each follower is designed. Using the Lyapunov stability theory, sufficient conditions are derived such that all the followers can track the leader. Finally, some numerical simulation results are presented to demonstrate the effectiveness of the proposed consensus protocol.